Fit for purpose - developing a software platform to support the modern challenges of data linkage in Western Australia - Eitelhuber, Tom Walter; Thackray, James; Hodges, Steve; Alan, Janine (International Journal of Population Data Science, 2018)
The Western Australia Data Linkage System (WADLS) is maintained and operated by the WA Data Linkage Branch (DLB) at the Western Australian Department of Health. DLB has pioneered a number of data linkage innovations, including the facilitation of genealogical research via the Family Connections system and streamlined data delivery via the Custodian Administered Research Extract Server. DLB’s latest innovation is a new data linkage system called “DLS3”, which improves DLB’s capability and capacity to handle the increasing volume and complexity of its routine operations. DLS3 was built entirely in-house and customised to meet the specific challenges that DLB has encountered throughout over twenty years of experience with a wide variety of linkages. This article describes the development and rollout of DLS3, including its design, architecture, benefits and limitations.